Conducting and Analyzing the Results of the Experimental Box Test of Retaining Wall Models Without Piles and on the Pile Foundation - Lisnevskyy, Maxim A.; Sukhorskyi, V. O. (Дніпропетровський національний університет залізничного транспорту імені академіка В. Лазаряна, Дніпропетровськ, 2015)
EN: Taking into consideration that the bearing capacity of the foundation may be insufficient, in the study it is assumed that pile foundation can be used to reduce the impact of the construction of new retaining structures on roads and railways near the existing buildings or in areas of dense urban development and ensure the stability of the foundation. To reduce the volume of excavation it is necessary to choose the economic structure of the retaining wall. To do this, one should explore stress-strain state (SSS) of the retaining walls, to develop methods to improve their strength and stability, as well as to choose the most appropriate method of their analysis. Methodology. In the design of retaining walls foundation mat and piles are considered as independent elements. Since the combined effect of the retaining wall, piles and foundation mat as well as the effect of soil or rock foundation on the structure are considered not fully, so there are some limitations in the existing design techniques. To achieve the purpose the box tests of retaining walls models without piles and with piles for studying their interaction with the surroundingsoil massif were conducted. Findings. Laboratory simulation of complex systems «surrounding soil – retaining wall– pile» was carried out and on the basis of the box test results were analyzed strains and its main parameters of the stress-strain state. Analysis of the results showed that the structure of a retaining wall with piles is steady and stable. Originality. So far, in Ukraine has not been carried out similar experimental box tests with models of retaining walls in such combinations. In the article has been presented unique photos and test results, as well as their analysis. Practical value. Using the methodology of experimental tests of the retaining wall models with piles and without them gives a wider opportunity to study stress-strain state of such structures.

UK: Беручи до уваги, що несуча здатність фундаменту може бути недостатньою, в науковій роботі передбачається, що пальовий фундамент може бути використаний для зниження впливу будівництва нових підпірних споруд на автомобільних і залізничних дорогах, біля вже існуючих будівель або в місцях щільної міської забудови, та гарантувати стабільність фундаменту. Для зниження обсягів земляних робіт потрібно обрати економічну конструкцію підпірної стінки. Для цього необхідно дослідити напружено-деформований стан (НДС) підпірних стін, розробити методи підвищення їх міцності та стійкості, а також обрати найбільш доцільний метод їх аналізу. Методика. При проектуванні підпірних стінок ростверк і палі вважаються незалежними елементами. Оскільки спільна дія підпірної стінки, паль, ростверку, а також вплив ґрунту або скельної основи на споруду враховуються не в повній мірі, тому є деякі обмеження в існуючих методах їх проектування. Для досягнення мети були проведені лоткові випробування моделей підпірних стін без паль і з палями з метою вивчення їх взаємодії із оточуючим масивом ґрунту. Результати. Вченими було виконано лабораторне моделювання складної системи «оточуючий грунт – підпірна стінка – паля». На основі результатів лоткових випробувань були проаналізовані деформації та основні параметри їх напружено-деформованого стану. Аналіз отриманих результатів показав, що конструкція підпірної стіни з палями є стійкою та міцною. Наукова новизна. До цього часу в Україні не було проведено аналогічних експериментальних лоткових випробувань із моделями підпірних стін у таких комбінаціях. В статті приведені унікальні фотографії та результати випробувань, а також їх аналіз. Практична значимість. Використання методики проведення експериментальних лоткових випробувань моделей підпірних стін із палями і без них дає більш широку можливість дослідження напружено-деформованого стану таких конструкцій.

RU: Принимая во внимание, что несущая способность фундамента может быть недостаточной, в научной работе предполагается, что свайный фундамент может быть использован для снижения влияния строительства новых подпорных сооружений на автомобильных и железнодорожных дорогах, возле существующих строений или в местах плотной городской застройки, и гарантировать стабильность фундамента. Для снижения объемов земляных работ нужно выбрать экономичную конструкцию подпорной стенки. Для этого необходимо исследовать напряженно-деформированное состояние (НДС) подпорных стен, разработать методы повышения их прочности и устойчивости, а также выбрать наиболее целесообразный метод их анализа. Методика. При проектировании подпорных стенок ростверк и сваи считаются независимыми элементами. Поскольку совместное действие подпорной стенки, свай, ростверка, а также влияние почвы или скального основания на сооружение учитываются не в полной мере, то есть некоторые ограничения в существующих методах их проектирования. Для достижения цели были проведены лотковые испытания моделей подпорных стен без свай и со сваями с целью изучения их взаимодействия с окружающим массивом грунта. Результаты. Учеными было выполнено лабораторное моделирование сложной системы «окружающий грунт – подпорная стенка – свая». На основании результатов лотковых испытаний были проанализированы деформации и основные параметры их напряженно-деформированного состояния. Анализ полученных результатов показал, что конструкция подпорной стены со сваями является устойчивой и прочной. Научная новизна. До сих пор в Украине не было проведено аналогичных экспериментальных лотковых испытаний с моделями подпорных стен в таких комбинациях. В статье приведены уникальные фотографии и результаты испытаний, а также их анализ. Практическая значимость. Использование методики проведения экспериментальных лотковых испытаний моделей подпорных стен со сваями и без них дает более широкую возможность исследования напряженно-деформированного состояния таких конструкций.
Проведення та аналіз результатів експериментального лоткового випробування моделей підпірної стіни без паль і на пальовому фундаменті
Проведение и анализ результатов экспериментального лоткового испытания моделей подпорной стены без свай и на свайном фундаменте
M. Lisnevskyy: ORCID 0000-0002-5550-8253; V. Sukhorskyi: ORCID 0000-0002-9072-9107
Keywords: retaining wall; pile foundation; box tests; soil massif; stability and strength of structure; comparative analysis of options; підпірна стінка; пальовий фундамент; лоткові випробування; грунтовий масив; стійкість та міцність конструкції; порівняльний аналіз варіантів; подпорная стенка; свайный фундамент; лотковые испытания; грунтовый массив; устойчивость и прочность конструкции; сравнительный анализ вариантов; КТОФ